Essays in macroeconomics: Consumption behavior, price dynamics, and fiscal spending - Rasmus Bisgaard Larsen (University of Copenhagen, Department of Economics, 2020)
This PhD dissertation consists of three self-contained chapters in the field of macroeconomics. The first two chapters rely a large scanner data set from the United States. The data set contains detailed pricing and sales information from retail stores as well as comprehensive information on purchases made by a panel of households. Using these data, the first chapter studies the effect of households' income on the quality of their purchases and the implications for their consumption-savings behavior. The second chapter investigates how regional changes in government spending affect local retail prices. The third chapter documents that a change in government spending causes house prices to move in the same direction, which is rationalized in a dynamic stochastic general equilibrium (DSGE) model with love of variety and increasing returns to scale.
Keywords: 330